A Practical Application of Management and Organization Theory for the Academic Administrator - Baltz, Gerald W. (Academy of Management Review, 1976)
In this article the author examines the communication gap the exists between practitioners and theorists in the management and organizational fields and attempts to bridge this divide. He presents his case in hopes of demonstrating to academic administrators that having a recognition of management and organizational principals can be invaluable when managing change. He notes that being aware of these principals can help change come about more smoothly and achieve desired results more quickly. He presents a case that outlines how the application of ineffective management principals can slow the process of organizational change and present unnecessary problems for those in charge of implementing the change.